Corporate governance : a guide for students - Rezaee, Zabihollah, 1953- (Routledge, 2025)
"Corporate governance has become increasingly central to corporate reporting and management as businesses face growing pressure to address their responsibilities in sustainability and corporate accountability. The evolving focus on effective corporate governance has driven the introduction of new laws, regulations, standards, and best practices, reshaping its framework, principles, and functions. Business leaders and students must stay informed about these significant reforms and the associated accountabilities. This book offers a clear, accessible guide to the key regulations, laws, and best practices essential for robust governance and stakeholder protection. It covers the roles and responsibilities of all key players in corporate governance, including directors, management, auditors, accountants, legal counsel, and financial advisors. Taking a practical approach, the book explores topics such as financial markets, investor confidence, oversight, managerial, compliance, internal and external auditing, legal advisory functions, and performance reporting. It serves as a valuable resource for students and professionals seeking a comprehensive understanding of corporate governance responsibilities. Designed for both undergraduate and graduate levels, this book equips students with the knowledge and skills needed to become successful business leaders. It is an ideal reference for business colleges, accounting schools, and other corporate governance programs, with individual chapters adaptable for various accounting and business courses"-- Provided by publisher.
Keywords: Corporate governance.; elektronické knihy; electronic books